Inhibitory effect of compounds from Zingiberaceae species on human platelet aggregation - Jantan, Ibrahim; Raweh, Salwa M; Sirat, Hasnah Mohd; Jamil, Shajarahtunnur; Mohd Yassin, Y.H; Jalil, Juriyati; Jamal, Jamia Azdina (Elsevier, 2008)
Twelve compounds isolated from Alpinia mutica Roxb., Kaempferia rotunda Linn., Curcuma xanthorhiza Roxb., Curcuma aromatica Valeton and Zingiber zerumbet Smith (Family: Zingiberaceae) and three synthesized derivatives of xanthorrhizol were evaluated for their ability to inhibit arachidonic acid- (AA), collagen- and ADP-induced platelet aggregation in human whole blood. Antiplatelet activity of the compounds was measured in vitro by the Chrono Log whole blood aggregometer using an electrical impedance method. Among the compounds tested, curcumin from C. aromatica, cardamonin, pinocembrine and 5,6-dehydrokawain from A. mutica and 3-deacetylcrotepoxide from K. rotunda showed strong inhibition on platelet aggregation induced by AA with IC50 values of less than 84 Î¼M. Curcumin was the most effective antiplatelet compound as it inhibited AA-, collagen- and ADP-induced platelet aggregation with IC50 values of 37.5, 60.9 and 45.7 Î¼M, respectively.